Implementation of Legal Culture toward Law Enforcement of Child Trafficking (Comparative Study of Indonesia and Australia) - Nasution, Eva Syahfitri; Santoso, Topo; Marlina, Marlina; Rosmalinda, Rosmalinda (Talenta Publisher, 2023)
This paper aims to analyze the influence of legal culture on criminal law enforcement in Indonesia and the implementation of legal culture on law enforcement for the crime of trafficking in children by conducting comparative studies in Indonesia and Australia. This research is qualitative and descriptive and uses literature studies to obtain secondary data. This research is limited only to how the implementation of legal culture affects enforcing the law on the crime of trafficking in children by conducting comparative studies in Indonesia and Australia. From the research, it was found that the legal culture is very influential on law enforcement in a country. When implemented in law enforcement, the effectiveness of the legal culture can be seen. Law enforcement itself has three concepts, namely the total concept (full enforcement concept), which is full (full enforcement concept). A comparison of the legal culture in enforcing the law on the crime of trafficking in children between Indonesia and Australia can be seen from the first two perspectives, from the cultural point of view of law enforcement officers. Second, it can be seen from the legal culture of Indonesian society that most of them still adhere to a patriarchal culture, while Australia adheres to what is called an egalitarian culture.